Intracoronary brachytherapy for in-stent restenosis of drug-eluting stents - Nisha Ohri, MD; Samin Sharma, MD; Annapoorna Kini, MD; Usman Baber, MD; Melissa Aquino, MS; Swathi Roy, MBBS; Ren-Dih Sheu, PhD; Michael Buckstein, MD, PhD; Richard Bakst, MD (Advances in Radiation Oncology, 2016)
Purpose: Given the limited salvage options for in-stent restenosis (ISR) of drug-eluting stents (DES), our high-volume cardiac catheterization laboratory has been performing intracoronary brachytherapy (ICBT) in patients with recurrent ISR of DES. This study analyzes their baseline characteristics and assesses the safety/toxicity of ICBT in this high-risk population. Methods and materials: A retrospective analysis of patients treated with ICBT between September 2012 and December 2014 was performed. Patients with ISR twice in a single location were eligible. Procedural complications included vessel dissection, perforation, tamponade, slow/absent blood flow, and vessel closure. Postprocedural events included myocardial infarction, coronary artery bypass graft, congestive heart failure, stroke, bleeding, thrombosis, embolism, dissection, dialysis, or death occurring within 72 hours. A control group of patients with 2 episodes of ISR at 1 location who underwent percutaneous coronary intervention without ICBT was identified. Unpaired t tests and χ2 tests were used to compare the groups. Results: There were 134 (78%) patients in the ICBT group with 141 treated lesions and 37 (22%) patients in the control group. There was a high prevalence of hyperlipidemia (>95%), hypertension (>95%), and diabetes (>50%) in both groups. The groups were well-balanced with respect to age, sex, and pre-existing medical conditions, with the exception of previous coronary artery bypass graft being more common the ICBT group. Procedural complication rates were low in the control and ICBT groups (0% vs 4.5%, P = .190). Postprocedural event rates were low (<5%) in both groups. Readmission rate at 30 days was 3.7% in the ICBT group and 5.4% in the control group (P = .649). Conclusions: This is the largest recent known series looking at ICBT for recurrent ISR of DES. ICBT is a safe treatment option with similarly low rates (<5%) of procedural and postprocedural complications compared with percutaneous coronary intervention alone. This study establishes the safety of ICBT in a high-risk patient cohort.